The Effect of Phosphorus Fertilization and Zinc spraying on some Phenotypic and Physiological Indicators and Productivity in Sesame Plant Sesamum indicum L. (Journal of Hama University, 2026)
The research was carried out in Al-Drouqiat village, Lattakia, Lattakia University for the season 2023-2024 to study some phenological and physiological characteristics of sesame plant under the influence of five levels of phosphorus fertilization (0, 40, 60, 80, 100) kg of triple superphosphate fertilizer containing 46% phosphorus pentoxide P2O5/ha and four concentrations of zinc spray (0, 30, 60, 90) mg of zinc sulfate fertilizer Zn2SO4/L.       The experiment was carried out according to a completely randomized block design with a single split plot arrangement and three replicates. The main blocks included phosphorus fertilization, while the secondary blocks included spraying zinc.       The results showed that the phosphorus fertilization level of 100 kg 46% TSP P2O5/ha was significantly superior to all other fertilization levels with the lowest average of number of days required to start flowering (44.25 days), number of days required to complete maturity (116.17 days) and highest average of leaf surface area (0.80 m2), leaf surface area index (8.04) and plant productivity (30.61 g).       The zinc spray concentration of 60 mg Zn2SO4/L significantly outperformed the other spray concentrations with the lowest average for number of days required to start flowering (45 days), number of days required to complete maturity (118.20 days), while the spray concentration of 90 mg Zn2SO4/L outperformed with the highest average for the trait of leaf surface area (0.64 m), leaf surface area index (6.35) and plant productivity (24.26 g) and the differences were not significant at the 60 mg Zn2SO4/L concentration for the plant productivity trait, and it reached (23.48 g).       The interaction (100 kg 46% TSP P2O5/h × 60 mg Zn2SO4/L) achieved a significant superiority with the lowest value of number of days required to start flowering, number of days required to complete maturity, while the interaction (100 kg P2O5/h × 90 mg Zn2SO4/L) achieved a significant superiority with the highest value of leaf surface area, leaf surface area index and the highest value of the plant productivity.
Keywords: sesame, triple superphosphate, zinc sulfate, leaf area index, plant productivity.